Benchmarking as a Tool to Enhance Strategic Management in the Hotel Industry - Dimitrios BELIAS; Ioannis ROSSIDIS; Labros VASILIADIS; Christos PAPADEMETRIOU (Communications of International Proceedings, 2021)
The modern socio-economic conditions and the ever-increasing demands for higher growth rates shape the perpetual need to improve the management of the hotel industry. The intense competition of the international environment constitutes vital the need to identify good practices in order to achieve high levels of efficiency and effectiveness. Both the international and the domestic market may offer highly efficient tools for the identification of good practices. The increasingly popular benchmarking tool may prove to be ideal for the transfer of know-how. Benchmarking refers to the technique used to evaluate an organisation's performance and to highlight advantages or disadvantages in a competitive environment. This technique enables to better explain and predict the future competitiveness of an organization while favoring the identification of administrative areas that need improvement, in order to enhance its competitiveness and effectiveness. This article will examine the prospects of applying the Benchmarking technique to the hotel industry, exploring: the requirements of this particular project, the theoretical background to the technique in question, and the possibilities springing by its successful implementation.
Keywords: Strategic Management; Hotel Management; Global Environment.